Disruption of polycystin-L causes hippocampal and thalamocortical hyperexcitability. (26th November 2015) - Yao, Gang; Luo, Chong; Harvey, Michael; Wu, Maoqing; Schreiber, Taylor H.; Du, Yanjun; Basora, Nuria; Su, Xuefeng; Contreras, Diego; Zhou, Jing
Abstract : Epilepsy or seizure disorder is among the least understood chronic medical conditions affecting over 65 million people worldwide. Here, we show that disruption of the polycystic kidney disease 2-like 1 ( Pkd2l1 or Pkdl ), encoding polycystin-L (PCL), a non-selective cation channel, increases neuronal excitability and the susceptibility to pentylenetetrazol-induced seizure in mice. PCL interacts with β2-adrenergic receptor (β2AR) and co-localizes with β2AR on the primary cilia of neurons in the brain. Pkdl deficiency leads to the loss of β2AR on neuronal cilia, which is accompanied with a remarkable reduction in cAMP levels in the central nervous system (CNS). The reduction of cAMP levels is associated with a reduction in the activation of cAMP response element-binding protein, but not the activation of Ca 2+ /calmodulin-dependent protein kinase II, Akt or mitogen-activated protein kinases. Our data, thus, indicate for the first time that a ciliary protein complex is required for the control of neuronal excitability in the CNS.